Fortified milk supplementation improve vitamin D status, grip strength, and maintains bone density in Chinese premenopausal women - Kruger, Marlena C.; Chan, Yoke Mun; Lau, Chin Chin; Lau, Lee Ting; Chin, Yit Siew; Sherlock, Barbara Kuhn; Schollum, Linda M.; Todd, Joanne M. (Mary Ann Liebert, 2019)
This study compared the effects of a high-calcium vitamin D fortified milk with added FOS-Inulin versus regular milk on serum parathyroid hormone (PTH), vitamin D status, grip strength (GS), as well as bone density in Chinese premenopausal women over 52 weeks. Premenopausal women (n = 133), mean age 41 (±5.1) years were randomized into control (n = 66; regular milk at 500 mg calcium per day) or intervention (Int; n = 67; fortified milk at 1200 mg calcium, 15 μg vitamin D, and 4 g FOS-Inulin per day) groups. Assessments were at baseline, weeks 12, 24, 36, and 52 for changes in vitamin D status, levels of PTH, and GS. Bone mineral densities (BMDs) of the lumbar spine (LS), femoral neck (FN), and whole body (WB) were assessed at baseline and week 52 using GE Lunar iDEXA (GE Healthcare, Madison, WI). At baseline, WB lean mass was positively associated with LS BMD (r = 0.30, p < 0.001) and FN BMD (r = 0.33, p = 0.003). Baseline 25(OH) vitamin D3 levels were 48.6 and 53.2 nmol/L (p = 0.57), respectively, and after the 12 months at 60.8 nmol/L (Int) versus 55.0 nmol/L (controls; p < 0.05 for change from baseline for both groups; no difference between groups at week 52). PTH levels decreased in both groups compared to baseline (p < 0.001), with no significant difference between groups. WB bone mineral content (BMC) and FN Z-score increased significantly in the Int group (p = 0.024 and p = 0.008). GS was positively associated with body weight, increasing in both groups over 52 weeks. Fortified milk improved vitamin D status, WB BMC, and Z-score of the FN, while regular milk maintained BMD. In addition, vitamin D status and GS improved.